The impact of pregnancy on the pharmacokinetics of antiseizure medications: A systematic review and meta-analysis of data from 674 pregnancies - Schoretsanitis, Georgios; Deligiannidis, Kristina M.; Kasperk, Nicholas; Schmidt, Chiara Theresa; Kittel-Schneider, Sarah; Ter Horst, Peter; Berlin, Maya; Kohn, Elkana; Poels, Eline M.P.; Zutshi, Deepti; Tomson, Torbjörn; Spigset, Olav; et al. (Progress in Neuro-Psychopharmacology & Biological Psychiatry, 2024)
Objective: Increasing evidence suggests that the physiological changes of pregnancy may impact pharmacokinetics of antiseizure medications (ASM), and this may affect treatment outcomes. The aim of this study was to quantify the pregnancy impact on the ASM pharmacokinetics. Methods: A systematic literature search was conducted in PubMed/EMBASE in November 2022 and updated in August 2023 for studies comparing levels of ASM in the same individuals during pregnancy and in the preconception/postpartum period. Alteration ratios between the 3rd trimester and baseline were estimated. We also performed a random-effects meta-analysis calculating between-timepoint differences in mean differences (MDs) and 95% confidence intervals (95%CIs) for dose-adjusted plasma concentrations (C/D ratios). Study quality was assessed using the ClinPK guidelines. Results: A total of 65 studies investigating 15 ASMs in 674 pregnancies were included. The largest differences were reported for lamotrigine, oxcarbazepine and levetiracetam (alteration ratio 0.42, range 0.07–2.45, 0.42, range 0.08–0.82 and 0.52, range 0.04–2.77 respectively): accordingly, C/D levels were lower in the 3rd trimester for lamotrigine, levetiracetam and the main oxcarbazepine metabolite monohydroxycarbazepine (MD = -12.33 × 10−3, 95%CI = -16.08 to −8.58 × 10−3 (μg/mL)/(mg/day), p < 0.001, MD = -7.16 (μg/mL)/(mg/day), 95%CI = -9.96 to −4.36, p < 0.001, and MD = -4.87 (μg/mL)/(mg/day), 95%CI = -9.39 to −0.35, p = 0.035, respectively), but not for oxcarbazepine (MD = 1.16 × 10−3 (μg/mL)/(mg/day), 95%CI = -2.55 to 0.24 × 10−3, p = 0.10). The quality of studies was acceptable with an average rating score of 11.5. Conclusions: Data for lamotrigine, oxcarbazepine (and monohydroxycarbazepine) and levetiracetam demonstrate major changes in pharmacokinetics during pregnancy, suggesting the importance of therapeutic drug monitoring to assist clinicians in optimizing treatment outcomes.
CRIS-Team Scopus Importer:2026-04-08
Keywords: Antiseizure medications; Lamotrigine; Levetiracetam; Pharmacokinetics; Pregnancy; Therapeutic drug monitoring; Women's mental health